Spastic paraplegia preceding PSEN1‐related familial Alzheimer's disease. Issue 1 (2nd May 2021) - Chelban, Viorica; Breza, Marianthi; Szaruga, Maria; Vandrovcova, Jana; Murphy, David; Lee, Chia‐Ju; Alikhwan, Sondos; Bourinaris, Thomas; Vavougios, George; Ilyas, Muhammad; Halim, Sobia Ahsan; Al‐Harrasi, Ahmed; et al.
Abstract: Introduction: We investigated the frequency, neuropathology, and phenotypic characteristics of spastic paraplegia (SP) that precedes dementia in presenilin 1 ( PSEN1 ) related familial Alzheimer's disease (AD). Methods: We performed whole exome sequencing (WES) in 60 probands with hereditary spastic paraplegia (HSP) phenotype that was negative for variants in known HSP‐related genes. Where PSEN1 mutation was identified, brain biopsy was performed. We investigated the link between HSP and AD with PSEN1 in silico pathway analysis and measured in vivo the stability of PSEN1 mutant γ‐secretase. Results: We identified a PSEN1 variant (p.Thr291Pro) in an individual presenting with pure SP at 30 years of age. Three years later, SP was associated with severe, fast cognitive decline and amyloid deposition with diffuse cortical plaques on brain biopsy. Biochemical analysis of p.Thr291Pro PSEN1 revealed that although the mutation does not alter active γ‐secretase reconstitution, it destabilizes γ‐secretase‐amyloid precursor protein (APP)/amyloid beta (Aβn) interactions during proteolysis, enhancing the production of longer Aβ peptides. We then extended our analysis to all 226 PSEN1 pathogenic variants reported and show that 7.5% were associated with pure SP onset followed by cognitive decline later in the disease. We found that PSEN1 cases manifesting initially as SP have a later age of onset, are associated with mutations located beyond codon 200, and showed larger diffuse, cored plaques, amyloid‐ring arteries, and severe CAA. Discussion: We show that pure SP can precede dementia onset in PSEN1‐ related familial AD. We recommend PSEN1 genetic testing in patients presenting with SP with no variants in known HSP‐related genes, particularly when associated with a family history of cognitive decline.